Artistic-Methodological Research of Anwar Obidjan - Mukhtaraliyev Bahromjon Ilyasjon Ugli (Indonesian Journal of Cultural and Community Development, 2024)
This study investigates the importance of comic stories in the evolution of Uzbek prose, with a particular focus on the originality and critique of society embedded in Anwar Obidjon's work. Using biographical, structural, and psychological techniques, this study explores Obidjon's distinctive style, which is shaped by literary influences and traditions. Through the creation of comic characters, Obidjon skillfully exposes the ugliness of prevalent society, and provides reflections on contemporary issues. The findings contribute to a deeper understanding of comic storytelling and its role in societal critique, and offer implications for the advancement of literary theory and practice. Highlight: Anwar Obidjon's comic stories become a lens for exposing the ugliness of society, reflecting on contemporary issues. The utilization of biographical, structural, and psychological techniques provides insight into Obidjon's distinctive literary style. This study contributes to increased understanding of the role of comic stories in societal critique in Uzbek prose. Keywords : Comic Stories, Style, Artistic Skills, Personality, Composition